The Protestant Reformation as an Islamisation of Christianity in the Thought of Ziya Gökalp and Ali Shariati - Gil Guerrero, Javier (Religions, 2024)
Following Ziya Gökalp and Ali Shariati’s assertion that Protestantism arose due to the influence of Islam in Europe in the Middle Ages, this study discusses the different discourses elaborated by the Turkish and Iranian authors based on this idea. The controversies surrounding modernity, westernization, colonialism, and Islam were a constant in their writings, despite the different geographical and historical circumstances. This paper discusses the logic of Gökalp and Shariati’s claim that Protestantism was Islamized Christianity. The aim is to provide a detailed perspective on how this claim illuminates their broader thinking about civilization, culture, and religion.